1993
DOI: 10.1097/00006842-199303000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise and the placebo effect: a controlled study.

Abstract: An experiment was conducted with 48 healthy young adults engaged in a supervised 10-week exercise program to determine whether a placebo effect is involved within the exercise-psychological enhancement connection. Based on an expectancy modification procedure, one-half of the subjects were led to believe that their program was specifically designed to improve psychological well-being (experimental condition) whereas no such intervention was made with the second half (control condition). Expectations for psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 16 publications
4
80
3
Order By: Relevance
“…The introduction of a 'placebo stimulus' was rejected owing to the obvious nature of FES intervention, and the placebo effects of exercise regimes per se. 41,42 Thus, any perception of well being or benefit derived from FES application may be attributed to a 'placebo effect'. 42 Alternatively, perception of benefit may be attributed to social participation 41,42 (opportunities for social interaction or additional clinical attention).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of a 'placebo stimulus' was rejected owing to the obvious nature of FES intervention, and the placebo effects of exercise regimes per se. 41,42 Thus, any perception of well being or benefit derived from FES application may be attributed to a 'placebo effect'. 42 Alternatively, perception of benefit may be attributed to social participation 41,42 (opportunities for social interaction or additional clinical attention).…”
Section: Discussionmentioning
confidence: 99%
“…41,42 Thus, any perception of well being or benefit derived from FES application may be attributed to a 'placebo effect'. 42 Alternatively, perception of benefit may be attributed to social participation 41,42 (opportunities for social interaction or additional clinical attention). As there was also an impression of contrary effects within the CON group (adjustment to injury, possibly explained by a perception of denial of a therapeutic benefit), these preliminary observations suggest that unblinded research in the rehabilitation setting (but not necessarily the FES protocol per se) may interact with the well being of the recently injured patient.…”
Section: Discussionmentioning
confidence: 99%
“…For example, media reports of the positive effects exercise has on mood are a possible source of expectancy, as are personal experiences and anecdotal reports. Desharnais et al (1993) compared two groups of participants that took part in a ten-week exercise programme, and one group was provided with information about the psychological benefits of exercise. This group reported significantly higher self-esteem and reported better psychological well-being in the middle and at the end of the ten-week exercise programme compared with the control group, who received no additional information about exercise effects on mood.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been demonstrated that non-blinded patients exaggerate the effects size by 0.56 standard deviations and that the effect is even larger in trials on interventional procedures, such as acupuncture 11, 12 . This bias may be caused by patients’ expectations of treatment effect and information given to them before the treatment 13 . Patients may also report symptoms depending on their “hunches” about treatment being effective or they may give answers they believe are “correct” or expected from them, for example, because it would have been impolite not to report improvement 11 .…”
Section: Blinding Of Patients Surgeons Outcome Assessors and Caregimentioning
confidence: 99%